An islamic animated infographic model for da'wah dissemination: a case study of prophets's sunnah in eating and drinking. - Nur Nazihah Rahim (2017)
Animated infographic has become increasingly popular due to its capacity to capture audience’s attention as opposed to words presentation alone. It is a useful tool for disseminating huge amount of information in appealing, and fun way in addition to making the process of gaining knowledge easier. This is because it allows complex information to be presented in a simpler manner. The human mind can process information quicker with visual imagery. In present day, individuals live in information-rich, digital era. This globalized era somehow creates some problems in terms of blending of information whereby confusion and difficulty in recalling information occur. Therefore, audience are not able to understand clearly the information that has been delivered. In spite of this, animated infographic could be an effective tool in conveying information successfully. Animated infographic has the capability to convey a great deal of information compared to still images. In addition, Islamic animated infographic for da’wah dissemination could be an alternative method to comprehend Islamic knowledge in this era of Information and Communication Technology (ICT). Researches which could help in the production of a good Islamic animated infographic model however, are still limited. Hence, this research focuses on the case study of da’wah dissemination on the subject of Prophet’s Sunnah in eating and drinking, more specifically, in the scope of da’wah dissemination in Malaysia. This research discusses creative and attractive approach to Islamic animated infographic model as an alternative method of da’wah. This research uses assessment by experts in the field of Design and Islamic Studies as well as prototype design of animated Islamic infographic as instruments for data collection. Then, survey forms are distributed to target respondents which are people who are involved in the field of design and Islamic studies. Subsequently, this target group is triangulated to capture different perspectives of the same phenomenon. Result from this research shows that Islamic animated infographic model is capable of conveying da’wah values in comprehensive manner whereby da’wah values are understood and practiced in daily lives. Islamic animated infographic model for da’wah dissemination is not just for the audience to accept it as mere entertainment, but to disseminate the da’wah as well. It could be concluded that animated infographic could be one of the alternative methods to disseminate da’wah as well as a creative and attractive approach in showing the beauty of Islam.